Love, loss, and what I wore - Beckerman, Ilene (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2005)
Ilene Beckerman has found a way to articulate something all women know: that our memories are often tied to our favorite cloths. In this original and eloquent book, Gingy as Ilene is called, tells the story of her life through the cloths she wore.
Keywords: Beckerman, Ilene, -- 1935-; Clothing and dress -- New York (State) -- History -- 20th century; New York (N.Y.) -- Biography